The Influence of Workload, Physical Work Environment, and Communication on Job Satisfaction in Cimahi City Education Service Employees - Reviana, Raisa; Ismail, Gurawan Dayona; Sudaryo, Yoyo; Wijaya, Fanji (International Journal of Business, Management and Economics, 2024)
The main aim of this research is to examine the influence of workload, physical work environment, and communication on the job satisfaction of Cimahi City Education Office employees. A sample of 45 employees was used for quantitative research. Used to test normality, multicollinearity, multiple regression, t-test, and F-test. Data was collected through questionnaires and observations. The research results show that workload does not significantly influence employee job satisfaction. For example, communication and the physical work environment positively affect employee job satisfaction. Based on hypothesis testing, H4 is considered acceptable, which means there is a significant relationship between Workload, Physical Work Environment, and Communication (at a significance level of 0.002 < 0.05). The results show that several suggestions can be made to increase employee satisfaction at the Cimahi City Education Office. First, to avoid stress and fatigue, the workload must be divided equally or by adding workers according to needs. Second, improving the physical work environment by having a separate building specifically for the Cimahi City Education Department is important. The space is narrow, and there is no special place for consultations. It is also hoped that there will be a special warehouse because employees can only be placed around the work desk, so the files are not organized. Neatly. Finally, it is important to improve communication between superiors, subordinates, and co-workers through communication training and regular discussion forums. Due to frequent miscommunication between colleagues, work is often hampered.